Model Pembelajaran Project Based Learning Sebagai Upaya Meningkatkan Motivasi Belajar Peserta Didik Dalam Pembelajaran Bahasa Indonesia Kelas IX SMP IT Darussalam, Kabupaten Tangerang - Siti Supriyati; Juli Yani; Agus Sulaeman (Politeknik Kampar, 2024)
This study was conducted to describe how the Project Based Learning (PjBL) learning model can improve student motivation and learning outcomes in Indonesian learning in class IX SMP IT Darussalam, Tangerang Regency. Project Based Learning (PjBL) is a learning model whose media is to use a project that will be done by students. The form of learning outcomes with this learning model is that students can explore, interpret, extract information independently and conduct assessments. The design of this learning model is used on complex problems needed by students in investigating and understanding them. The implementation of Project-based learning can make students more active and creative in learning activities, so as to encourage student motivation in learning. The steps in implementing the Project Based Learning model begin with determining fundamental questions, preparing project planning, preparing schedules, monitoring, testing results, and finally evaluating learning experiences. The results of research conducted in class IX of SMP IT Darussalam, Tangerang Regency, were obtained from primary data and secondary data. Primary data is data obtained directly from informants. Meanwhile, secondary data includes documentation data, archival records, and other physical devices relevant to the object of study. Based on these two data, positive results were obtained, namely by using the Project Based Learning learning model in Indonesian learning, especially in writing inspirational story texts, the motivation and learning outcomes of Class IX students of SMP IT Darussalam increased. Thus, this research is expected to be used as one of the solutions to problems in schools, especially in Indonesian learning.